Gendered extractivism in Uganda: implications for Just Transitions - Müller, Tobias (IOP Publishing, 2025)
Critical analyses of extractivism have demonstrated that it frequently involves interconnected gendered impacts on local communities. While gender equality has become an important concern in the literature on sustainability and economic development, more intersectional and decolonial feminist critiques of extractivism are only slowly entering mainstream debates even though they offer important perspectives for thinking about the socio-political challenges Just Transitions are likely to face, especially in African countries with weak governance systems. This paper contributes to the understanding of the potential gendered impact of putative just transition programmes in Africa through the analyses of different gendered impacts in three zones of resource extraction in Uganda, namely mining in Karamoja, a sugar cane plantation in Mabira Forest and oil extraction via the East African Crude Oil Pipeline (EACOP). Employing an intersectional and decolonial feminist lens, the paper identifies three gendered dimensions of extractivist impacts, namely sexual violence, barred access to basic necessities and dispossession of land. It is vital to take these challenges seriously in order to avoid reproducing such gendered impact in attempts to achieve a Just Transition in Uganda and countries with similar socio-economic profiles.
Keywords: extractivism; gender; Just Transition; Global South; Uganda; EACOP